Synthesis and Antidiabetic Evaluation of N’-Benzylidenebenzohydrazide Derivatives by In Silico Studies - Yusuf Syaril Alam; Pratiwi Pudjiastuti; Saipul Maulana; Nur Rahmayanti Afifah; Fahimah Martak; Arif Fadlan; Tutik Sri Wahyuni; Syukri Arief (Universitas Gadjah Mada, 2023)
Two new of N’-benzylidenebenzohydrazide (NBB) derivatives were successfully synthesized and yielded 50–58%. FTIR, ESI-MS, 1H-NMR and 13C-NMR were used to investigate the characteristic of NBB derivates. The structure and relationship of NBB derivatives into α-glucosidase and α-amylase as good targets for diabetes treatment were evaluated using in silico screening. Molecular Mechanics-Poisson Boltzmann/Generalized Born Surface Area (MM-PB/GBSA) was used to calculate the free binding energy (ΔGbind (MM-GBSA)) of NBB to α-glucosidase and α-amylase receptors showed that the results of −0.45 and −20.79 kcal/mol respectively. In the ortho position, NBB derivatives exhibited electron donating groups (EDG like -OCH3, -OH and -Cl with binding free energies of −21.94, −6.71 and 21.94, respectively, and acarbose, a native ligand energy of 32.62 kcal/mol. In addition, the binding free energy of N-2-(-OCH3, -OH and -Cl)-NBB to the α-amylase receptor showed the number of −39.33, −43.96, −42.81, respectively and −46.51 kcal/mol in comparing with a native ligand. As a result, it was found that all the NBB derivatives were able to interact with several amino acids in the α-glucosidase cavity as well as the native ones, including Ala281, Asp282, and Asp616. NBB and native ligand showed similar interaction between α-amylase with Gly110 amino acid residue.